Czech version of the Emotion Regulation Skills Questionnaire (ERSQ): Psychometric evaluation and network model in an adult clinical sample - Klocek, Adam; Řiháček, Tomáš; Cígler, Hynek (Psychological assessment, 2022)
The Emotion Regulation Skills Questionnaire (ERSQ, 27 items) is an instrument designed to measure nine emotion regulation skills. This study examined the psychometric properties and longitudinal network structure of the Czech translation of the ERSQ in the clinical sample (primarily mood or neurotic disorders). Czech patients N = 427 completed the ERSQ weekly during treatment. The data were analyzed using confirmatory factor analysis (CFA) and network modeling. The CFA supported an eight-dimensional factor solution (with merged Acceptance and Tolerance subscales). The subscales' internal consistency ranged from ωh = .669 (Bodily sensations) to ωh = .859 (Acceptance/Tolerance). The factor structure was invariant across genders, two age groups, and seven measurement waves (invariance tested as an assumption for network analysis). The longitudinal network model indicated the existence of perceptive and modulatory clusters of emotional regulation skills and revealed the central role of Modification, Bodily sensations, and Readiness for confrontation in emotional regulation. The Czech translation of the ERSQ is a psychometrically sound instrument comparable to the original version. Despite the high internal consistency of the total score (ωtot = .910), the ERSQ is not recommended for use as a unidimensional instrument. (PsycInfo Database Record (c) 2022 APA, all rights reserved).
Keywords: Psychometrics; Czech Republic; Humans; Česká republika; ženské pohlaví; Reproducibility of Results; Adult; Emotional Regulation; psychometrie; mužské pohlaví; reprodukovatelnost výsledků; emoční regulace; lidé; Female; průzkumy a dotazníky; Male; Surveys and Questionnaires; dospělí